The Role of Perceived Usefulness and Perceived Ease-of-Use toward Satisfaction and Trust which Influence Computer Consumers’ Loyalty in China - Nicholas Wilson; Keni Keni; Pauline Henriette Pattyranie Tan (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
This study was commenced in order to examine the impact that both perceived usefulness and perceived ease-of-use had toward consumers’ loyalty within the computer industry in China, either directly or indirectly through satisfaction and trust. This current study utilized the survey method; questionnaires were selected as the instrument which would be used to collect all of the data from the respondents. All of the questionnaires were electronically distributed through an online survey site to a total of 400 respondents, who originated from, or were living in, five cities in China. After gathering and assessing all of the collected data, a total of 346 items of data were deemed usable, thus enabling these sets of data to be further analyzed by this study. All of these data were further analyzed using the partial least squares-structural equation modeling (PLS-SEM) method using SmartPLS 3.3.2 software. Based on the results obtained through the data’s analyses, the authors would like to conclude that both perceived usefulness and perceived ease-of-use had a positive and significant impact on customer satisfaction, trust and customer loyalty within China’s computer industry. Furthermore, in this study, both customer satisfaction and trust have been found to positively mediate the impact of perceived usefulness and perceived ease-of-use toward customer loyalty; trust serves as a better mediator compared to satisfaction. Meanwhile, this study contributed to the expansion and the enrichment of the literature in the field of marketing by thoroughly examining the implementation of the technology acceptance model (TAM) in predicting customer loyalty within China’s computer industry.